Center for agri-food nanotechnology - Fabello, Jeff Ray E.; Bo-ot, Luis Maria T. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
The Center for Agri-food Nanotechnology is an education and research and development facility for the engineering, interdisciplinary science of nanotechnology and its applications on food and agriculture. It shall be a joint project between UPLB, DOST and PCIEERD and shall be the housing facility of the UPLB Nanotechnology Program. Architectural programming was based on existing local and international precedents, and publications on agri-food nanotechnology, particularly Kuzma and VerHage's Nanotechnology in Agriculture and Food Production: Anticipated Applications. The theoretical framework revolves around two approaches in the study of nanotechnology, (1) the bottom-up approach by Feynman and, (2)the top-down approach of Taniguchi, two key features in the field. The designer shall find the balance between the two approaches in design of the facility -going back-and-forth between macro- and micro-analysis of design considerations to produce a cohesive amalgamation of ideas. Working under the philosophy of technological appropriateness and innovation, the Center for Agri-food Nanotechnology shall be designed with adherence to the requirements of specially constructed facilities and equipment, as well as to the physical context, which is the UPLB campus. The resulting design shall enable innovation not only in architecture, but also in the field of science it was designed for.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman